Secular trends in physical fitness and performance of university track and field athletes - Matsumoto, Y.; Kohmura, Y.; Nakamura, A.; Takanashi, Y.; Aoki, K. (Scientific Journal of Sport and Performance, 2023)
There are only few records of physical fitness data for athletes. This study aimed to explore the secular trends in physical fitness data of student athletes and the relationship of fitness parameters with the results of intercollegiate sports competitions. We used the physical fitness data of male students belonging to the Juntendo University Athletics Club from 1999 to 2019. The analysed parameters were height, weight, chest circumference, skinfold thickness, grip strength, vertical jump, sidestep, and sit and reach test. The ekiden results were examined in relation to data on medium- and long-distance activities with reference to the ranking. The study results suggested no difference in the skinfold thickness of the upper extremity across the events, except for throwing events. Grip strength declined gradually in sprints, hurdles, and jumping events, while it was high in throwing events. Vertical jump records declined over time in all events and remained at low levels in middle- and long-distance events. Sidestep improved among males in the general population, while it remained the same among all athletes. A relationship was found between grip strength and vertical jump, which are indices of muscle strength and power, and competitive results obtained in middle- and long-distance races.